2021
DOI: 10.3390/antibiotics10101239
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of tet(X6)-Carrying Tigecycline-Resistant Acinetobacter baumannii Isolates with a New Capsular Type at a Hospital in Taiwan

Abstract: Dissemination of multidrug-resistant, particularly tigecycline-resistant, Acinetobacter baumannii is of critical importance, as tigecycline is considered a last-line antibiotic. Acquisition of tet(X), a tigecycline-inactivating enzyme mostly found in strains of animal origin, imparts tigecycline resistance to A. baumannii. Herein, we investigated the presence of tet(X) variants among 228 tigecycline-non-susceptible A. baumannii isolates from patients at a Taiwanese hospital via polymerase chain reaction using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
(94 reference statements)
0
13
0
1
Order By: Relevance
“…53 Recently co-exictence of tet(X6) and bla OXA-72 , located on chromosome and plasmid respectively, have been reported in A. baumannii clinical isolates. 54 Another suggested mechanism involved in tigecycline resistance is an outer membrane protein, AbuO, that is homologe of TolC.…”
Section: S-adenosyl-l-methionine-dependent Methyltransferase Encodedmentioning
confidence: 99%
“…53 Recently co-exictence of tet(X6) and bla OXA-72 , located on chromosome and plasmid respectively, have been reported in A. baumannii clinical isolates. 54 Another suggested mechanism involved in tigecycline resistance is an outer membrane protein, AbuO, that is homologe of TolC.…”
Section: S-adenosyl-l-methionine-dependent Methyltransferase Encodedmentioning
confidence: 99%
“…Ecological niches in which plasmid-encoded TIG resistance tet (X) genes have been detected are shown in Table 1 . Clearly, there is increasing evidence of plasmid-encoded TIG resistance tet (X) genes reported in countries across Europe, Asia, United States, South America, and Africa involving humans, food animals, including chickens, pigs, ducks, pigeons, geese, and cattle, as well as companion animals, food animal products (meats), aquaculture and environment such as soil, livestock-farm water, wastewaters, sewages, and wildlife as reservoirs of MTR ( Bai et al, 2019 ; Chen et al, 2019a , b , 2020 , 2021 ; He et al, 2019 ; Sun C. et al, 2019 , 2020 ; Sun J. et al, 2019 ; Cao et al, 2020 ; Cui et al, 2020 , 2021b ; Ding et al, 2020 ; Du et al, 2020 ; He T. et al, 2020 ; Li et al, 2020 , 2021f ; Ma et al, 2020 ; Pan et al, 2020 ; Ruan et al, 2020 ; Song et al, 2020 ; Wang et al, 2020a , b ; Zhang et al, 2020b , 2021 ; Zheng et al, 2020 ; Cheng et al, 2021a , b ; Feng et al, 2021 ; Hirabayashi et al, 2021a , b ; Hsieh et al, 2021 ; Li et al, 2021e , f ; Lu et al, 2021 ; Marathe et al, 2021 ; Martelli et al, 2021 ; Mohsin et al, 2021 ; Soliman et al, 2021 ; Sun et al, 2021a , b ; Tang et al, 2021 ; Wang et al, 2021f , g ; Xu et al, 2021 ; Yu Y. et al, 2021 ; Wu et al, 2022 ; Zhai et al, 2022 ). We further demonstrate this, through the specific reservoirs in which plasmid-borne transmissible tet (X) and tmexCD-toprJ genes have been detected as shown in Table 2 .…”
Section: Distribution Reservoirs and Traits Of Mobile Tigecycline Res...mentioning
confidence: 99%
“…In essence, those in contact with animals (including veterinarians) are potential disseminators of MTR gene-containing organism into the public and veterinary hospital environments where these organisms have become a major nosocomial threat. Unfortunately, the organisms in ESKAPE ( Enterobacter , Staphylococcus , Klebsiella , Acinetobacter , Pseudomonas aeruginosa , and Escherichia coli ) group which are the most troubling pathogens associated with nosocomial and community infections worldwide ( De Oliveira et al, 2020 ), have been reported as traffickers of MTR genes ( He et al, 2019 ; Wang et al, 2019 ; Cui et al, 2020 ; Hsieh et al, 2021 ). However, the transmission of MTR at the human-animal interface is of more concern in developing countries because humans, especially those in rural areas, live in close contact with livestock ( Alonso et al, 2017 ).…”
Section: Possible Mobile Tigecycline Resistance Gene Transfer Mode An...mentioning
confidence: 99%
See 2 more Smart Citations